Pengaruh Strategi Pembelajaran Langsung, Terhadap Hasil Belajar Siswa - Ratu Ajeng Galuh Pitaloka; Reviani .; Gusmaneli . (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to analyze and empirically examine the effect of direct learning strategies on students’ learning outcomes. Direct learning strategy is a teacher-centered approach that emphasizes the delivery of material in a systematic, structured, and gradual manner, starting from concept explanation, example demonstration, guided practice, and independent practice. This strategy is considered effective, especially in helping students understand conceptual and procedural materials clearly and systematically. However, in practice, its effectiveness still needs to be proven through systematic research.This study employs a quantitative approach using a quasi-experimental design. The research subjects consist of students divided into two groups: an experimental group that is taught using the direct learning strategy and a control group that uses conventional teaching methods. Data collection techniques include learning outcome tests to measure students’ cognitive abilities, supported by observation and documentation to strengthen the research data. The research instruments have been tested for validity and reliability to ensure the accuracy of the data obtained. Data analysis was conducted using statistical tests, such as the t-test, to determine the differences in learning outcomes between the two groups. The results indicate that there is a significant difference between students who are taught using the direct learning strategy and those who are taught using conventional methods. The experimental group shows a higher improvement in learning outcomes compared to the control group. This finding indicates that the direct learning strategy has a positive effect on students’ learning outcomes. Based on these findings, it can be concluded that the direct learning strategy is effective in the learning process, particularly in improving students’ conceptual understanding and basic skills. Therefore, teachers are encouraged to consider the use of direct learning strategies as an alternative approach in teaching to enhance the quality of students’ learning outcomes. This study is expected to contribute to the development of more effective and efficient learning strategies in the field of education.